An Assessment of the Influence of Corporate Governance Principles on Growth of Savings and Credit Co-Operative Societies in KISII County, Kenya (Global Journal of Management and Business Research, 2019)
The purpose of this study was to assess the influence of corporate governance principles on the growth of savings and credit cooperatives societies in Kisii County, Kenya. The recent past had witnessed decreased growth of societies due to alarming rate of dormant Savings and credit corporative societies within Kisii County a situation that was attributed to poor corporate governance principles practiced by Savings and credit corporative societies. The specific objectives considered in this study were: influence of Accountability, participation, inclusivity, and transparency on growth of SACCOs. The theory that was considered for this study was agency theory. The researcher adopted crosssection research design. The target population was 172 management officials of the deposit taking savings and credit corporative societies within Kisii County. Census method was used to obtain the sample size. The researcher used questionnaires as the research instruments for the purpose of collecting data from the respondents for the study. Validity of the study involved the researcher discussing with the supervisors on how the questionnaire was to be tailored to ascertain accurate information from the respondents for data analysis, and the reliability of the research instruments was measured by Cronbach's Alpha. Adequate reliability level was attained. The study targeted a total of 172 sampled SACCO management officials on whom the questionnaires were administered.